Integrasi Kesehatan Mental Pelaut dalam Sistem Manajemen Keselamatan Kapal: Tantangan dan Peluang di Industri Pelayaran - Gustian, Huske Dwi; Evri, Evri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Seafarers’ mental health is increasingly recognized as a strategic determinant of maritime safety, as growing evidence indicates that psychosocial risks such as fatigue, chronic stress, violence, and harassment directly contribute to human error in ship operations. Although the International Maritime Organization (IMO), through Resolution MSC.560(108), has explicitly positioned mental health as an integral component of maritime safety, its integration into Ship Safety Management Systems (SMS) remains structurally and culturally constrained, particularly in developing countries. In these contexts, limited digital learning infrastructure, uneven compliance across shipping companies, institutional capacity gaps, and persistent cultural stigma surrounding mental health constitute tangible barriers to effective regulatory implementation at the operational level.This article aims to analyze the positioning of seafarers’ mental health within the SMS framework, identify context-specific integration challenges in developing countries, and explore strengthening mechanisms through training and Learning Management Systems (LMS). A qualitative policy-oriented narrative review was conducted, examining ISM Code (2018), MSC.560(108), MLC 2006, STCW Code, operational guidelines, and national maritime training modules.The findings reveal a persistent implementation gap between strengthened international norms and shipboard SMS practices, where mental health continues to be treated primarily as an individual welfare issue rather than a systemic safety risk. In developing-country settings, this gap is exacerbated by limited access to digital LMS platforms, normalization of fatigue within maritime culture, and underreporting driven by stigma and rigid hierarchical structures onboard. These findings substantiate the argument that integrating mental health into SMS requires a measurable paradigm shift from compliance-based safety toward psychosocial risk-based and human-centered safety embedded within hazard identification, reporting mechanisms, and safety audits. Theoretically, this article advances socio-technical maritime safety scholarship by structurally incorporating mental health into safety management discourse. Practically, it provides policy directions and implementation strategies for shipping companies, regulators, and maritime education institutions in developing countries seeking to strengthen sustainable safety.